Exploring Electric Transmission Operation with Cognitive Work Analysis Models. (September 2021) - Üreten, Ece; Olatoye, Olamide; Kelly, Adrian; Burns, Catherine
Electric power networks are regarded as complex socio-technical systems as they incorporate a wide number of tasks and dynamic data that needs to be monitored continuously. This preliminary study investigated the work environment of electric power transmission and the related control tasks performed by the system operators. These findings shall be incorporated into the design of an ecological interface to improve situation awareness, reduce cognitive workload, and especially support novice operators in training.